A green method for polybutylene succinate recycling: Depolymerization catalyzed by lipase B from Candida antarctica during reactive extrusion. (July 2015) - Jbilou, Fouzia; Dole, Patrice; Degraeve, Pascal; Ladavière, Catherine; Joly, Catherine
Graphical abstract: Highlights: PBS depolymerization by enzymatic hydrolysis at molten state was investigated. High PBS depolymerization rate was obtained by lipase in a twin screw extruder at 120 °C. A yield of 44% of monomers (succinic acid) was obtained by 10% of lipase. PBS recycling can be performed by enzymatic extrusion in order to replace the methods using solvents. Abstract: This study aims to investigate a "green" recycling route for polybutylene succinate (PBS) based on reactive extrusion in the presence of an enzyme catalyzing the hydrolysis of this aliphatic polyester: lipase B from Candida antarctica . This enzyme was chosen due to its thermal stability, since reactive extrusion was performed at 120 °C (i.e. above PBS melting temperature). PBS hydrolysis was measured after extrusion at 120 °C either in a single or a twin screw extruder, in the presence of 0–10 wt% C. antarctica lipase for 5 or 30 min. In a twin screw extruder, the residual activity of the enzyme was still 38% or 24%, after 5–30 min extrusion at 120 °C, respectively. For instance, the weight average molecular weight ( Mw ) of PBS decreased from 82, 000 to 4500 g mol −1 after extrusion for 5 min in the presence of 1% wt of lipase. The highest yield of free succinic acid release (44%) was obtained following a 30 min extrusion in the presence of 10 wt% of C. antarctica lipase. The drastic decrease in weight average molecular weight of PBS after enzymatic hydrolysis caused an only 10 °C decrease in the melting temperature.